Effect of Natural Feed Provision on the Growth of Koi Fish Seed - Mohamad Harun; Hasim Hasim; Rully Tuiyo (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2018)
This study aims to determine the effect of natural feeding of Tubifex sp, Moina sp, mosquito larvae on the growth of seeds of koi fish (Cyiprinus carpio). This study uses a Completely Randomized Design (CRD) using Analysis of Variance (ANOVA) with 3 treatments and 4 replications. The results showed that the best absolute length and weight growth was shown in A Tubifex sp treatment, namely absolute length 0.8 cm and absolute weight 0.51 gram. The results of analysis of various growth length and weight of koi fish have a very significant effect on growth, followed by the Least Significant Difference Test (LSD) for weight and length growth obtained at each significantly different treatment. Keywords: koi; Cyprinus carpio; Tubifex sp; Moina sp; mosquito larvae; growth.